The Role of Fatwa TV in The Dissemination of Hadith - Naufal, Usamah Abdurrahman; Sandy, Medional; Ikhlas, Al; Al Islami, Sulthan Fadzil; Hendra, Tomi (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
This research aims to analyze and discover the virtues of disseminating hadith, examine the role of Fatwa TV in spreading hadith, and analyze the implications of hadith dissemination by Fatwa TV. The rapid development of technology and mass media has provided both opportunities and challenges for the dissemination of Islamic teachings, particularly hadith. Television, as an influential media platform, plays a crucial role in disseminating religious information to the wider Utilizing a qualitative approach, this study seeks to analyze and discover the virtues of disseminating hadith, examine the role of Fatwa TV in spreading hadith, and analyze the implications of hadith dissemination by Fatwa TV. The research findings indicate that Fatwa TV functions as a platform for learning hadith, offering religious question-and-answer sessions, providing contextual explanations, and digitalizing content. The virtues of disseminating hadith through Fatwa TV include perpetual rewards, receiving Allah's mercy and prayers from His creatures, and complying with Allah's command for Muslims to seek knowledge. Positive implications of hadith dissemination by Fatwa TV include better understanding of hadith content, ability to distinguish between authentic and weak hadiths, improved understanding of correct Islamic law, and motivation to practice the Sunnah. This research underscores the importance of media's role in effectively and accurately disseminating Islamic teachings.